What rhymes with snake? : a word and picture flap book - Brown, Rick, 1946- (New York : Tambourine Books, 1994)
Simple text and movable illustrations present paired words that rhyme, such as "hen" and "pen."
Horn Book Magazine
Bulletin Of The Center For Children's Books
1.3
K-3
Keywords: Vocabulary -- Juvenile literature; Toy and movable books -- Specimens; English language -- Spelling; Vocabulary; Toy and movable books; English language -- Spelling; Vocabulary; Toy and movable books